Konsep Etika Belajar dalam Kitab Ta’limul Muta’allim Karya Syaikh al-Zarnuji dan Tanbihul Muta’allim Karya KH. Ahmad Maisur Sindi al-Thursidi - Asfiya, Muhammad Farih; Abdillah, Nanang; Rafsanjani, Anugerah Zakya (FATAWA: Jurnal Pendidikan Agama Islam, 2023)
Many Islamic educational experts have given serious attention to studying the concept of learning ethics, including al-Zarnuji and Ahmad Maisur Sindi al-Thursidi, who were Muslim intellectual thinkers who were competent in developing Islamic educational thought in their time. This research aims to determine the similarities and differences in thoughts in the Book of Ta'limul Muta'allim by Syaikh Al-Zarnuji and the Book of Tanbihul Muta'allim by KH. Ahmad Maisur Sindi Al-Thursidi. The results of the research show that the similarities between both regarding ethics in learning are that you must be in a state of purity, pray before studying, be istiqamah in studying, face the direction of the Qibla, be serious in studying, respect the teacher, be polite, not hurt the teacher's feelings, and ask permission if necessary. Meanwhile, according to al-Thursidi, the difference is that students must be serious about studying, memorize and learn knowledge in stages, divide their time so they can fulfill their time rights, understand knowledge seriously and write down the knowledge they have gained, repeat lessons more often. Which has been studied mainly at night, and must apply the knowledge gained to others so that the knowledge becomes useful.